2018
DOI: 10.3390/en11020270
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Potential of Rice Straws as a Supplementary Fuel in Very Small Power Plants in Thailand

Abstract: Agricultural residue is a major raw material for renewable energy production, particularly heat production, in Thailand. Meanwhile, the process-based residue, such as bagasse, rice husk, wood residue, palm fiber, palm shell, and saw dust, is used as a fuel for energy production in the agro-industry. Hence, this study is intended to assess the net potential and capacity of alternative agricultural residues, specifically rice straws, to serve as the supplementary fuel for very small power plants (VSPPs) in Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…Because the rice residue generated located in rain-fed filed can be burned in the long period from the after harvesting to before tillage (October to April for next year) while the rice residue generated located in irrigated-fed filed was immediately burned after harvesting, in order to present a result as accurate as possible. This information indicated that there is a large gap between the seasonal variation of burned area from MCD64A1 and the previous studies [2,45] (shown in Figure 3) and the PM2.5 emission or rice residue burned (shown in Figure 5). It can be explained that the rice residue burned was calculated from 4 parameters which included the harvested area (ha), biomass load (t/ha), fraction of rice residue subjected to open burning (unitless) and combustion factor (unitless).…”
Section: Atmosphere 2018 9 X For Peer Review 11 Of 22mentioning
confidence: 66%
See 4 more Smart Citations
“…Because the rice residue generated located in rain-fed filed can be burned in the long period from the after harvesting to before tillage (October to April for next year) while the rice residue generated located in irrigated-fed filed was immediately burned after harvesting, in order to present a result as accurate as possible. This information indicated that there is a large gap between the seasonal variation of burned area from MCD64A1 and the previous studies [2,45] (shown in Figure 3) and the PM2.5 emission or rice residue burned (shown in Figure 5). It can be explained that the rice residue burned was calculated from 4 parameters which included the harvested area (ha), biomass load (t/ha), fraction of rice residue subjected to open burning (unitless) and combustion factor (unitless).…”
Section: Atmosphere 2018 9 X For Peer Review 11 Of 22mentioning
confidence: 66%
“…This information indicated that there is a large gap between the seasonal variation of burned area from MCD64A1 and the previous studies [2,45] (shown in Figure 3) and the PM 2.5 emission or rice residue burned (shown in Figure 5). It can be explained that the rice residue burned was calculated from 4 parameters which included the harvested area (ha), biomass load (t/ha), fraction of rice residue subjected to open burning (unitless) and combustion factor (unitless).…”
Section: Atmosphere 2018 9 X For Peer Review 11 Of 22mentioning
confidence: 67%
See 3 more Smart Citations